Perceptual and Neurophysiological Effects of Treated and Untreated Hearing Loss in Older Adults - McClannahan, Katrina Sue (My University, 2017)
The purpose of this dissertation work was to examine the impact of auditory deprivation in the form of age-related hearing loss (ARHL) and auditory stimulation in the form of hearing aid use, on the neural registration and abilities to use sound for higher level cognitive tasks, in older adults (aged 55-75). Three groups were examined: 1) NH: older adults with clinically normal hearing, 2) u-HL: peers with bilateral mild to moderate/moderately- severe sensory-neural hearing loss who have never worn hearing aids and 3) t-HL: peers with a similar amount of hearing loss, but who have been treated through binaural amplification (hearing aids). Participants completed two sessions: 1) Behavioral tests: Audiometry, cognitive screening, quality of life questionnaires, nonverbal IQ test, speech recognition in quiet and noise, and tests of verbal working memory function (both auditory and visual); 2) Electrophysiology: Evoked potentials (P1-N1-P2) recorded in response to a speech syllable presented at two different sound levels (equal sound pressure level (SPL) and equal sensation level (SL)). All three groups performed similarly on tests of speech perception in noise, working memory and nonverbal IQ, but differed on self-report measures of hearing handicap. Both hearing loss groups indicated greater reported greater hearing handicap (HHIE) than NH groups. Additionally, individuals with untreated hearing loss showed a positive relationship between working memory performance and speech understanding in noise. Neural measures indicated significant morphological differences (latency and amplitude) between groups, but only when the stimuli were presented at equal SPL. Once audibility was accounted for (equal SL levels) these differences were not present, suggesting group differences were due to audibility, and not central changes secondary to auditory deprivation. Results highlight the importance of the audibility of sound, and suggest that early sound processing and later use of sound for processes involved in communication is not permanently affected by mild to moderate/moderately-severe ARHL.
Thesis (Ph.D.)--University of Washington, 2017-03
Keywords: Aging; Electrophysiology; Hearing Loss; Audiology; Speech